(untitled) (Fiep Bulletin - online, 2016)
Tuberculosis (TB) is a disease of world-wide proportions that can be prevented and treated with highly efficient and affordable medicines supplied by the Brazilian Health Care System. Nevertheless, there is no prospect of obtaining its eradication in the near future as a public health issue in Brazil, since 80% of the worldwide cases, which correspond to 50 million people, are concentrated in our country and 23 other developing countries. Despite the advances in the control of TB, Brazil is still one of the 22 priority countries for the World Health Organization (WHO), being part of the group that covers 80% of the global burden of TB. The objective of this research is to assess the profile of cases that underwent a Directly Observed Treatment in the year of 2012 in Foz do Iguaçu – PR. An epidemiological study with a quantitative approach was conducted. The epidemiological profile of the sick that underwent the Directly Observed Treatment in the year of 2012 was identified as follows: white male individuals with little schooling were the most affected. It concludes that the knowledge about these aspects constitutes important information for health care professionals so they can mobilize their efforts in ensuring the sick do complete their treatment, thus avoiding abandonment and death, events that impede the effective control of the disease.